Strategi pengurangan kehilangan pascapanen produk hortikultura - Mulyawanti, Ira; Suryana, Esty Asriyana (Analisis Kebijakan Pertanian, 2024)
Horticultural commodities are food products with the highest postharvest loss because physiological activity continues after harvest. Postharvest loss studies need to be conducted to identify the causes of postharvest losses of these commodities so that strategies can be developed to reduce them. The study was conducted through field observation, focus group discussions, interviews, and literature studies. Then, themes were extracted from the data, and the relationship between these themes and factors that influence the level of postharvest loss was analyzed. The study’s results showed that the main causes of horticultural product losses include inappropriate harvesting techniques and times, Good Handling Practice (GHP) not being appropriately implemented, suboptimal storage space quality, lack of access to postharvest technology, and inefficient supply chains. Alternative policies to reduce horticultural postharvest losses are implementing postharvest technology, simplifying the supply chain, and implementing processing technology. For this reason, partnerships among horticultural agribusiness actors (government and business entities) are needed to empower farmers and actors along the supply chain, promote the invention and dissemination of postharvest technologies to reduce loss and waste, improve distribution and marketing, and provide and rehabilitate agricultural infrastructures.